Analytical characteristics of a document flow of dissertations on library science in the USA and Canada - P. S. Romanov (Библиосфера, 2018)
The article discusses the results of studying a document flow of English-speaking dissertations in the field of library science, bibliography and bibliology, as well as information management for a centenary period. To solve the research tasks, a scientometric approach has been applied including sources, bibliometric, historical methods, as well as elements of the content analysis. The author has carried out a thematic selection of English-language dissertations from several foreign sources, in particular, databases by UMIProQuest Co and some others. The paper reveals development trends of library information science abroad for hundred years. The author compiled and published an annotated list of English-language theses on this topic with the translation into Russian.